Right ventricular electromechanical dyssynchrony in adults with repaired Tetralogy of Fallot - Bowen, Daniel; Kauling, Martijn; Loff Barreto, Bernardo; McGhie, Jackie; Cuypers, Judith; Szili-Torok, Tamas; Roos-Hesselink, Jolien; van den Bosch, Annemien (Frontiers in Pediatrics, 2023)
Background and purpose Electromechanical dyssynchrony, manifested by right bundle branch block and regional wall mechanical dysfunction, contributes to inefficient RV function in repaired Tetralogy of Fallot (ToF). This study aims to evaluate the synchronicity of multiple RV walls using two-dimensional multi-plane echocardiography (2D-MPE) in order to augment current understanding of the mechanisms behind RV dyssynchrony. Methods Sixty-nine adult ToF patients (aged 33 [23-45] years; 61% male) and twenty-five matched healthy controls underwent deformational analysis of the RV lateral, anterior, inferior and septal walls following 2D-MPE acquisitions. RV synchronicity was assessed by the intra-RV deformation delay between each basal RV wall and mid-septal segment in addition to mechanical dispersion calculated across four, six and eight segments (MD). Results All RV wall-septum delays plus MD-4 and MD-6 indices were significantly greater in ToF patients compared to healthy controls (p <0.001-0.03). In ToF patients, the lateral and anterior RV walls were last to reach peak deformation and anterior wall longitudinal strain was lower (p = 0.001). Post systolic shortening of at least one RV wall segment was identified in 19 (28%) ToF patients. Despite similar ECG characteristics, lateral and anterior wall-septum delays were significantly longer in patients with greater degrees of dyssynchrony (73 [37-108]ms vs 37 [0-63]ms, p = 0.006; 91 [52-116]ms vs 41 [1-69]ms, p = 0.013), although RV ejection fraction (RVEF) was not significantly lower. MD-4 and MD-8 indices displayed moderate negative associations with RVEF, strengthened by inclusion of lateral wall longitudinal strain (r = 0.64/0.65; p ≤0.01). Conclusion RV dyssynchrony in ToF is characterised by electromechanical delays between the lateral, anterior and septal walls, with anterior wall dysfunction likely associated with surgical repair of the RV outflow tract. Prospectively, 2D-MPE may have an emerging role evaluating RV mechanical response to electrical resynchronisation therapy.